Dominant Role of Peroxiredoxin/JNK Axis in Stemness Regulation During Neurogenesis from Embryonic Stem Cells. (April 2014) - Kim, Sun‐Uk; Park, Young‐Ho; Kim, Jin‐Man; Sun, Hu‐Nan; Song, In‐Sung; Huang, Song Mei; Lee, Sang‐Hee; Chae, Jung‐Il; Hong, Su; Sik Choi, Sung; Choi, Seung‐Cheol; Lee, Tae‐Hoon; et al.
Abstract Redox balance has been suggested as an important determinant of "stemness" in embryonic stem cells (ESCs). In this study, we demonstrate that peroxiredoxin (Prx) plays a pivotal role in maintenance of ESC stemness during neurogenesis through suppression of reactive oxygen species (ROS)‐sensitive signaling. During neurogenesis, Prx I and Oct4 are expressed in a mutually dependent manner and their expression is abruptly downregulated by an excess of ROS. Thus, in Prx I−/− or Prx II−/− ESCs, rapid loss of stemness can occur due to spontaneous ROS overload, leading to their active commitment into neurons; however, stemness is restored by the addition of an antioxidant or an inhibitor of c‐Jun N‐terminal kinase (JNK). In addition, Prx I and Prx II appear to have a tight association with the mechanism underlying the protection of ESC stemness in developing teratomas. These results suggest that Prx functions as a protector of ESC stemness by opposing ROS/JNK cascades during neurogenesis. Therefore, our findings have important implications for understanding of maintenance of ESC stemness through involvement of antioxidant enzymes and may lead to development of an alternative stem cell‐based therapeutic strategy for production of high‐quality neurons in large quantity. Stem Cells2014;32:998–1011